TEACHING WRITING DESCRIPTIVE TEXT THROUGH GENRE BASED APPROACH:(A Case Study Research at a Junior High School in Bandung) - Lestari, Astri Indah (2015)
The aims of this study are to investigate the effects of the implementation of GBA in developing students' writing ability and to discover students' responses toward the implementation of GBA in their English class. This study employed qualitative method through a single case study approach to gather the data. The participants of this study were thirty-six students of the 7th grade students at one junior high school in Bandung. The GBA implementation was held for four weeks, which lasted ninety minutes for each meeting. The data of this study were obtained through classroom observation, students' written text, and questionnaire. The effects of the GBA implementation were gathered from classroom observation and students' written text analysis in terms of social function, schematic structure, and linguistic features of descriptive text. The result showed that the GBA had good effects in developing the students' writing ability, especially in writing descriptive text as reflected in students' writing achievement in final text product. Furthermore, the data from questionnaire showed that 93% of students gave positive responses toward the implementation of GBA and 7% of students gave negative responses toward the approach. Therefore, GBA is recommended to be implemented in teaching writing and other researchers can also implement GBA to teach other texts and skills. Keywords: teaching writing, descriptive text, genre based approach Penelitian ini bertujuan untuk melihat efek dari pengimplementasian GBA dalam mengembangkan kemampuan menulis siswa dan untuk mengetahui pendapat siswa mengenai pengimplementasian GBA dalam kelas bahasa Inggris. Penelitian ini menggunakan metode kualitatif dan pendekatan studi kasus tunggal untuk mengumpulkan data. Partisipan dari penelitian ini adalah 36 siswa kelas 7 pada satu sekolah menengah pertama di Bandung. Pengimplementasian GBA dilakukan selama empat minggu, masing-masing pertemuan 90 menit. Data penelitian diperoleh melalui observasi kelas, tulisan siswa, dan juga angket. Pengaruh dari pengimplementasian GBA didapat dari observasi kelas dan analisis hasil tulisan siswa dalam hal fungsi sosial, struktur teks, dan fitur linguistik dari teks deskriptif. Hasil dari penelitian ini menunjukkan bahwa GBA dapat membantu siswa untuk mengembangkan kemampuan mereka dalam menulis teks deskriptif seperti yang terlihat dari hasil tulisan siswa pada produk teks yang terakhir. Selain itu, data dari angket menunjukkan bahwa hampir seluruh siswa memberikan tanggapan positif terhadap pengimplementasian GBA dan beberapa siswa memberikan tanggapan negatif pada pendekatan tersebut. Oleh karena itu, GBA direkomendasikan untuk diimplementasikan pada proses pengajaran menulis dan untuk penelitian selanjutnya dapat mengimplementasikan GBA untuk mengajarkan teks dan keterampilan yang berbeda. Kata kunci: mengajar menulis, teks deskriptif, genre based approach